COMPARATIVE EFFECTIVENESS RESEARCH AND ITS APPLICATION TO NURSING EDUCATION - Claire Su-Yeon Park (Journal of Learning and Teaching in Digital Age, 2016)
This in-depth integrative literature review aimed to investigate comparative effectiveness research (CER) methodologies applicable to nursing research and to propose a CER design relevant to nursing education. Integration and synthesis were conducted from August 20 to December 15, 2013 and from October 20 to December 05, 2015 using electronic databases and refereed published books. The key words were “comparative effectiveness research,” “education,” “patient outcomes,” “effectiveness,” “cost-effectiveness,” and “efficiency.” All selected literatures were initially scrutinized by the principal investigator in terms of scientific rigor and then synthesized on an ongoing basis. CER methodologies in nursing research were presented to be significant in terms of enabling the distinctiveness of the nursing profession to stand out. Three CER methodologies applicable to nursing research—a Pragmatic Clinical Trial, Observational Comparative Effectiveness Research and Cost Effectiveness Research—revealed each of their distinguishable strengths and weaknesses compared to the Randomized Controlled Trial. For ethical considerations, the importance of ensuring “equipoise” was identified. Lastly, in a head to head comparison of two nursing education programs, a single blind, randomized crossover study design was proposed as a type of Pragmatic Clinical Trial utilizing cost-utility analysis. A mixed method Analysis of Covariance and a Doubly Multivariate Repeated Analysis of Covariance were suggested as relevant statistical analyses. Considering that CER is still inchoate in nursing research and nurse scientists’ endeavors to address the gap are urgent, this study is compelling in that it proposed a rigorous CER design not only directly applicable to nursing education, but also to other disciplines in education.